Spinal Cord Series and Cases - Alexander, Marcalee; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
Spinal Cord Series and Cases: Clinical Management in Spinal Cord Disorders is an international, online-only journal which publishes high quality case reports, small case series, pilot and retrospective studies, perspectives, Pulse survey articles, Point-counterpoint articles, correspondences and book reviews. It specialises in material that addresses all aspects of life for persons with spinal cord injuries or disorders including psychosocial, vocational, medical, social, environmental, wellness and of course spinal cord anatomy, physiology and lesions (injury and disease). The journal covers practical topics for practitioners who treat patients with spinal cord injuries and to highlight educational issues. It will also cover topics related to professional and personal providers of care for persons with SCIs. The journal strongly supports the use of the International Data Sets, the International Standards to Document Remaining Autonomic Function after Spinal Cord Injury and the International Standards for the Neurologic Classification of SCI in submitted publications and also encourages papers that highlight the educational aspects of these documents. Spinal Cord Series and Cases: Clinical Management in Spinal Cord Disorders follows a continuous publishing model, with available content published every week and is an official journal of the International Spinal Cord Society. Spinal Cord Series and Cases$1 (Bsister journal Spinal Cord is a specialised, international journal that has been publishing since 1963. It appears monthly online and in print and accepts contributions on spinal cord anatomy, physiology, management of injury and disease, and the quality of life and life circumstances of people with a spinal cord injury. Spinal Cord is multi-disciplinary and publishes contributions across the entire spectrum of research ranging from basic science to applied clinical research. It focuses on high quality original research, systematic reviews and narrative reviews. Subscribers can purchase a subscription to Spinal Cord, which includes full access to Spinal Cord Series and Cases: Clinical Management in Spinal Cord Disorders.s
Keywords: Medicine; Human physiology; Neurosciences; Neurochemistry; Human anatomy; Neuropsychology; Biomedicine, general; Neurosciences; Anatomy; Human Physiology; Neurochemistry; Neuropsychology